Classification of Fake Accounts on Followers of Averentcos Cosplay Rental Account on Instagram Using the K-Nearest Neighbor (KNN) Method - Mufrodi, Hafidz; Nur Wakhidah,; Prind Triajeng Pungkasanti, (Jurnal Transformatika, 2026)
Technological advances have given business people several options to develop their business. One of them is using Instagram social media as a promotional tool. However, using social media as a promotional medium has its own problems. Fake accounts spread on Instagram can reduce the reach of business accounts. Until now, there are more than millions of fake accounts. Instagram continues to increase its efforts to detect and delete these fake accounts. This study was conducted to be able to classify accounts suspected of being fake accounts on the followers of the averentcos account using the k-NN method. The data used were 500 follower accounts with various backgrounds. This study used several variables, namely Profile Photo, Username Length, Number of Name Words, Similarity of Name to Username, Bio Length, External Links, Public Accounts, Number of Posts, Number of Followers, Number of Followed so that accuracy of 86,666% can be achieved.